Elastogenesis Correlates With Pigment Production in Murine Aortic Valve Leaflets - Hutcheson, Joshua D.; Schlotter, Florian; Creager, Michael D.; Li, Xiaoshuang; Pham, Tan; Vyas, Payal; Higashi, Hideyuki; Body, Simon C.; Aikawa, Masanori; Singh, Sasha A.; Kos, Lidia; Aikawa, Elena (Frontiers in Cardiovascular Medicine, 2021)
Objective – Aortic valve (AV) leaflets rely on a precise extracellular matrix (ECM) microarchitecture for appropriate biomechanical performance. The ECM structure is maintained by valvular interstitial cells (VICs), which reside within the leaflets. The presence of pigment produced by a melanocytic population of VICs in mice with dark coats has been generally regarded as a nuisance as it interferes with histological analysis of the AV leaflets. However, our previous studies have shown that the presence of pigment correlates with increased mechanical stiffness within the leaflets as measured by nanoindentation analyses. In the current study, we seek to better characterize the phenotype of understudied melanocytic VICs, explore the role of these VICs in ECM patterning, and assess the presence of these VICs in human aortic valve tissues. Approach and Results – Immunofluorescence and immunohistochemistry revealed that melanocytes within murine AV leaflets express phenotypic markers of either neuronal or glial cells. These VIC subpopulations exhibited regional patterns that corresponded to the distribution of elastin and glycosaminoglycan ECM proteins, respectively. VICs with neuronal and glial phenotypes were also found in human AV leaflets and showed ECM associations similar to those observed in murine leaflets. A subset of VICs within human AV leaflets also expressed dopachrome tautomerase, a common melanocyte marker. A spontaneous mouse mutant with no aortic valve pigmentation lacked elastin fibers and had reduced elastin gene expression within AV leaflets. A hyperpigmented transgenic mouse exhibited increased AV leaflet elastin fibers and elastin gene expression. Conclusions – Melanocytic VIC subpopulations appear critical for appropriate elastogenesis in mouse AVs, providing new insight into the regulation of AV ECM homeostasis. The identification of a similar VIC population in human AVs suggests conservation across species.